Grenfell of Labrador : a biography - Rompkey, Ronald (University of Toronto Press, 1991)
Wilfred Thomason Grenfell arrived in Newfoundland in 1892. At first an evangelical missionary of the Royal National Mission to Deep Sea Fishermen, he raised funds and founded a network of hospitals, nursing stations, schools, and home industries. Also considers contributions of Lady Grenfell and officers of Grenfell Mission.